KEJADIAN AMENOREA PADA AKSEPTOR KB SUNTIK DI BPM CH SUSILOWATI, TREKO, MUNGKID TAHUN 2014 - Resti Astida Putri; Siti Chunaeni (JURNAL KEBIDANAN, 2015)
Hormonal contraceptive injections kind in Indonesia has become widely used as an effective, user and practical, relatively inexpensive and safe. However, injections also have many side effects such as weight gain, headaches, and breast tenderness, also often cause menstrual disorders such as amenorrhea. In the complaint acceptor kb injection, menstrual disorders are more dominant than others ie amenorrhoea by 30%. In brief, the purpose of this study was to determine the relationship of the use of the type of injectable contraceptive acceptors incidence of amenorrhea in injecting in Bpm Ch Susilowati, Treko, Mungkid 2014.         This research is analytic survey using cross sectional design. The population in this study are all active acceptor CICs in BPM Ch Susilowati, Treko, Mungkid April 42 acceptors. The sampling technique in this study was non-random with accidental sampling.The results showed in the univariate variables are most respondents use any type of contraceptive DMPA injection acceptors were 26 (61.9%) and the majority of respondents experienced amenorhea incidence of 25 acceptors (59.5%). Contingency coefficient test results obtained significance p value ≤ 0.05 is 0.003. This suggests an association with the use of injectable contraceptives types amenorhea events. The magnitude of the strength of the relationship is 0.412 which means the strength of the relationship is moderate.             For midwives are expected to improve counseling about the benefits and side effects of hormonal contraceptives that one of them is in the form of menstrual cycle disorders amenorrhoea sehngga can reduce anxiety acceptor with respect to adverse events occurred.